Developing vocabulary knowledge among low achievers: Mobile Augmented Reality (MAR) practicality - Jalaluddin, Ilyana; Ismail, Lilliati; Darmi, Ramiza (International Association of Computer Science and Information Technology, 2020)
Difficulty in learning gives huge impact to the process of language discovery among school children. LINUS students are categorized in this group and regarded as Low Achiever (LA) regardless of their education level. Currently, schools are provided with traditional learning materials such as textbook prepared by the Ministry of Education and it is up to the teachers’ own creativity and initiative to turn the materials into a more interesting learning source [1], [2]. However, depending solely on these learning materials alone is not enough as these children will easily lose their attention as they become bored and finally lost interest to proceed with the learning process [3]. Therefore, there is a need to utilize the elements of technology in order to motivate and facilitate these LINUS students in learning vocabulary in English. This experimental study aimed to explore the effectiveness of using mobile augmented reality (MAR) application in vocabulary learning among LINUS students. 45 students were involved and the development of MAR in vocabulary learning in this study was investigated based on the ADDIE Instructional Design (ID) method as a framework. As a form of measurement, British Picture Vocabulary Scale (BPVS) III was used and findings showed that there was a significant improvement in the post test after 6 months of MAR implementation. Although this study showed an encouraging results, there was still lack of skills in terms of writing the words learnt via augmented reality. The results of this study provide the discussion on the practicality of using Augmented Reality to help the struggling learners to cope with acquiring and learning English language in ESL context.